LIAF 2022. Fantasmagoriana - Francesco Ragazzi, Francesco Urbano, Helga-Marie Nordby, Marianne Hultman, Kurt Schwitters; Ragazzi, Francesco; Urbano, Francesco (Nordnorsk kunstnersenter, 2022)
This book is the catalogue of the XVII edition of the Lofoten International Art Festival, the longest-running biennial in Scandinavia. Entitled Fantasmagoriana, the exhibition took place at the North Norwegian Art Centre in Svolvaer and at five sites in Kabelvåg, above the Arctic Circle, in 2022. The volume describes the works exhibited by the thirty-seven artists participating in the festival, as well as the research background, residency programs, and preview projects in Venice and Oslo that preceded the inauguration of the biennial. Texts by Francesco Urbano Ragazzi, Marianne Hultman, Helga-Marie Nordby are included in the catalogue, together with a short novel by Kurt Schwitters which was translated into English and Norwegian for the first time on this occasion. Participating artists: Nora Al-Badri, Bassam Al-Sabah, Marianne Berenhaut, Alessandra Cianchetta, Kirstine Colban Aas, Pauline Curnier Jardin, Tomaso De Luca, Nolan Oswald Dennis, Cheryl Donegan, Kaare Espolin Johnson, Gaia Fugazza, Aage Gaup, Kenneth Goldsmith, Shadi Habib Allah, Auriea Harvey, Susan Te Kahurangi King, Tomáš Kajánek, Lars Laumann, Sonia Leimer, Olof Marsja, Mary Haugen, Jonas Mekas, Haroon Mirza, Raffaela Naldi Rossano, Eivind H. Natvig, New Mineral Collective, Thebe Phetogo, Christine Rebet, Sille Storihle, Tine Surel Lange, Emma Talbot, Tsai Ming-liang, Stan VanDerBeek, Rimaldas Vikšraitis, Elina Waage Mikalsen, Jennifer West.